ANALISIS SUMBER BAHAYA BAGI PENYELENGGARAAN WISATA BENCANA LAVA TOUR DI TAMAN NASIONAL GUNUNG MERAPI - Aziza, Tsania; Zanuar, Seila; Nisa, Najwa Zahratun; Prameswari, Amanda Rara; Putri, Anjali Nurizki; Shina, Eliza Nazwa; Fadhlillah, Refi; Rahmafitria, Fitri (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Mount Merapi National Park is a conservation natural tourism area located in a disaster-prone area because there is the most active volcano and is included in the Ring of Fire area. In its use, lava tour natural tourism has safety risks that need to be considered. This study aims to identify sources of danger in the Mount Merapi National Park area, especially in lava tour tourism activities. The research method carried out is a descriptive qualitative and HIRARC analysis techniques. The descriptive qualitative method used is to collect and analyze data with interviews related to hazards in tourist destinations. The results showed that there are 4 very high risks (extreme) and 5 high risks (high) that need to be controlled by tour managers. Risk control efforts that have been carried out have not been fully effective in preventing accidents. It is recommended to tour managers to limit visitor capacity, appeal to tourists to be careful when standing, use seatbelts, repair safety equipment regularly, and provide cushioning on the jeep frame.